1980
DOI: 10.1044/jshr.2304.722
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility of Time-Compressed Sentential Stimuli

Abstract: Time-compressed monosyllables have been studied relative to the assessment of central auditory disorders. In certain instances, sentential stimuli may be more useful than word lists in central auditory testing, particularly when results may be contaminated by concomitant peripheral hearing losses. Central Institute for the Deaf (CID) and Revised CID sentence lists and a contrived sentential approximation task were presented to 96 normal hearing young adults at time-compression ratios of 0%, 40%, 60%, and 70%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…These manipulations were designed to keep the statistics of the acoustic stimulus within the range of original vocalizations, in order to best drive responses in A1. Psychophysical studies in humans found that speech comprehension is preserved over temporal dilations up to a factor of 2 (Beasley et al 1980;Dupoux and Green 1997;Foulke and Sticht 1969). Here, we used a scaling factor of 1.25 or 0.75, similar to previous electrophysiological studies (Gehr et al 2000;Wang et al 1995), and also falling within the statistical range of the recorded vocalizations.…”
Section: Discussionmentioning
confidence: 99%
“…These manipulations were designed to keep the statistics of the acoustic stimulus within the range of original vocalizations, in order to best drive responses in A1. Psychophysical studies in humans found that speech comprehension is preserved over temporal dilations up to a factor of 2 (Beasley et al 1980;Dupoux and Green 1997;Foulke and Sticht 1969). Here, we used a scaling factor of 1.25 or 0.75, similar to previous electrophysiological studies (Gehr et al 2000;Wang et al 1995), and also falling within the statistical range of the recorded vocalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehension of time-compressed (TC) speech was determined by using a variety of speech compression methods (6,7). These studies have shown that comprehension in normal Ss begins to degrade around a compression of 0.5.…”
Section: Discussionmentioning
confidence: 99%
“…The critical frequency band of the temporal envelope for normal speech comprehension is between 4 and 16 Hz (3, 4); envelope details above 16 Hz have only a small [although significant (5)] effect on comprehension. Across this low-frequency modulation range, comprehension does not usually depend on the exact frequencies of the temporal envelopes of incoming speech, because the temporal envelope of normal speech can be compressed in time down to 0.5 of its original duration before comprehension is significantly affected (6,7). Thus, normal brain mechanisms responsible for speech perception can adapt to different input rates within this range (see refs.…”
mentioning
confidence: 99%
“…Compressed speech approximates rapidly produced speech and is characterized by a higherfrequency speech envelope. Compressed speech is more difficult to perceive compared with conversational speech (Beasley et al, 1980) and has been used in a previous study investigating cortical phase-locking to the speech envelope (Ahissar et al, 2001).…”
Section: Methodsmentioning
confidence: 99%